The fury ; and, Dark reunion - Smith, L. J. (Lisa J.) (Smith, L. J. (Lisa J.). Vampire diaries, 2007)
Collects the final two volumes of "The Vampire Diaries," in which Elena sacrifices an immortal love to end the constant strife between two vampire brothers who love her, and then raises them from the dead to save her town from an unknown evil.